Prediction of Water Loss During Potato Vacuum Frying Process - Supardan, Muhammad Dani; Satriana, Satriana (Jurnal Rekayasa Kimia & Lingkungan, 2007)
Vacuum frying may be a good alternative for the production of dehydrated fruit and vegetable slices. In this study, a relationship between water losses with frying time during vacuum frying process of potato chips has been developed. A first order kinetic model was used, in which drying rate constant is a function of the main process variables, i.e. oil temperature, sample thickness and vacuum pressure. The experimental data of Garayo and Moreira (2000) have been used to validate the model. Generally there was a good agreement between the calculated results and the experimental data. Then, the effect of initial water content and vacuum pressure has been studied.Keywords: kinetic model, potato, vacuum frying, water loss